Dental teleconsultation in COVID-19 time. Literature review - Li Pereyra, Carmen (2020)
The high transmissibility of the etiological agent SARS-CoV-2, led the dentist to be the health professional with the highest risk of contagion due to the face-to-face consultation where he is in contact with saliva and blood in addition to the use of aerosols. This has led to the use of technology and telecommunications as a tool for a remote consultation, being known as Teleodontology. The search criteria for scientific articles in electronic format have been based on publication time, presence of DOI, no language is excluded; obtained from sources such as PubMed, SciElo, Google Scholar. Carrying out the search in July 2020. In Peru, 70% of infections in dentists were during the face-to-face consultation, the legal and ethical aspect leads to distrust of carrying out a teleconsultation. This research work provides recommendations from the reason for consultation, informed consent, prescription, patient follow-up, as well as the tele-education approach. CONCLUSIONS: Teleodontology is one of the first options to provide consultation in cases that do not require a face-to-face consultation, however, the lack of a protocol, supporting laws and training has led to distrust in carrying it out.